Body and Social Interaction—The Case of Dance. Symbolic Interactionist Perspective - Byczkowska-Owczarek, Dominika (Qualitative Sociology Review, 2020)
The article aims at presenting the symbolic interactionism as a useful and flexible theoretical perspective in research on the human body. It shows the assumptions of symbolic interactionism in their relation to the human body, as well as explains how basic notions of this theoretical perspective are embodied—the self, social role, identity, acting, interacting. I depict the unobvious presence of the body in the classical works of George H. Mead, Anselm Strauss, Howard Becker, Erving Goffman, and in more recent ones, such as Bryan Turner, Ken Plummer, and Loïc Wacquant. I also describe the Polish contribution to the field, including research on disability, hand transplant, the identity of a disabled person, together with the influence of sport, prostitution as work, yoga, climbing, relationships between animals and humans based on gestures and bodily conduct, the socialization of young actors and actresses, non-heteronormative motherhood, and the socialization of children in sport and dance. In a case study based on the research on ballroom dancers, I show how to relate the theoretical requirements of symbolic interactionism with real human “flesh and bones.” I depict three ways of perceiving own bodies by dancers: a material, a tool, a partner; and, two processes their bodies are subjected to: sharpening and polishing a tool. I draw the link between the processual character of the body, of the symbolic interactionist theoretical perspective, and process-focused grounded theory methodology.